Invader complexes or generalist interactions? Seasonal effects of a disturbance gradient on plants and floral visitors - Agüero, Juan I. (2021)
Fil: Agüero, Juan I. Universidad de Buenos Aires. Facultad de Agronomía. Cátedra de Botánica General. Buenos Aires, Argentina.